2009
DOI: 10.1590/s1984-82502009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of the fermentation extract of the endophytic fungus Alternaria alternata isolated from Coffea arabica L.

Abstract: A total of 22 endophytic fungi isolated from coffee (Coffea arabica L.) were cultivated in vitro and their crude extracts tested. The screening was carried out using the agar diffusion method against Staphylococcus aureus, Escherichia coli and Candida albicans. The most effective isolate was Alternaria alternata, and subsequently, its extract was assayed. The total phenolic content was 3.44 μg GAE/mg of the crude extract. For the antibacterial and antifungal activity assays, minimum inhibitory concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 32 publications
(25 reference statements)
4
35
1
3
Order By: Relevance
“…We also found that ethyl acetate extracts of A. alternata mycelium and culture broth were more active against yeast (MIC ≤ 0.095 mg/mL) than against bacteria (MIC ranging from 0.095 to 25 mg/mL). Most of our MIC values were in range or slightly lower than those reported by Fernandes et al (2009) and by Ramesha et al (2013) for ethyl acetate extract of A. alternata against S. aureus, B. cereus, E. coli and P. aeruginosa (MIC = 0.02 mg/mL). Some of the antimicrobial compounds produce by fungi belonging to the genus Alternaria have been already identified.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We also found that ethyl acetate extracts of A. alternata mycelium and culture broth were more active against yeast (MIC ≤ 0.095 mg/mL) than against bacteria (MIC ranging from 0.095 to 25 mg/mL). Most of our MIC values were in range or slightly lower than those reported by Fernandes et al (2009) and by Ramesha et al (2013) for ethyl acetate extract of A. alternata against S. aureus, B. cereus, E. coli and P. aeruginosa (MIC = 0.02 mg/mL). Some of the antimicrobial compounds produce by fungi belonging to the genus Alternaria have been already identified.…”
Section: Discussioncontrasting
confidence: 57%
“…This endophyte may also have potential utility as antibacterial agent due to its capacity to inhibit significantly the bacteria B. cereus, B. subtilis, S. aureus and P. aeruginosa. Extracts of A. alternata inhabiting coffee plants (Fernandes et al 2009), silver trumpet tree (Sadananda et al 2011) and sweet wormwood (Qadri et al 2013) have been previously found to displayed antimicrobial activity against an array of bacteria and yeasts, including C. albicans (Qadri et al 2013). The various organic extracts from both A. alternata mycelium and cultured broth were also found to displayed different antimicrobial effects.…”
Section: Discussionmentioning
confidence: 99%
“…have previously shown antimicrobial activities against Gram positive and Gram negative bacteria, as well as fungi [38,52]. It is not known if the bioactivity from our endophytes is due to the compounds previously reported.…”
Section: Discussionmentioning
confidence: 81%
“…The regular occurrence of the Alternaria genera within C. roseus indicates that certain strains belonging to this genus may exhibit host specificity towards C. roseus. Additionally, Alternaria strains may have been selectively targeted due to their established production of antimicrobial compounds [38]. The other fungal genera represented in the endophyte community included Botryosphaeria sp.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic fungi have also drawn attention as potential producers of many products, including industrially interesting enzymes. Endophytic fungi exhibit a complex web of interactions with the host plants and have been extensively studied over the last several years as prolific sources of new bioactive natural products, including new enzymes with interesting properties for industrial application (Verza et al 2009;Borges et al 2009;Fernandes et al 2009). However, very few endophytic fungi have been reported as producers of lipase.…”
Section: Lipasesmentioning
confidence: 99%